Bibliometric Analysis Integrating Halal Supply Chain and Circular Economy Principles - Kuncorosidi Kuncorosidi; Muhamad Supria Wiguna (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2024)
Integrating halal supply chain and circular economy principles can create a sustainable and ethical business environment. This can be achieved through innovation and the application of technology to improve the efficiency of halal production and supply chain operations. The circular economy principles can promote the reuse and recycling of waste materials, reducing environmental impact and enhancing the economic value of resources. Innovation can be crucial in developing sustainable solutions to integrate halal supply chain and circular economy principles effectively. If you have any specific questions related to this topic please feel free to ask and I can suggest which bot can provide more detailed information.